2020
DOI: 10.1002/hep.31214
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Study of Hepatitis Delta Virus Infection at Secondary Care Centers: The Impact of Viremia on Liver‐Related Outcomes

Abstract: BaCKgRoUND aND aIMS: Hepatitis delta virus (HDV) infection is associated with fast progression to liver cirrhosis and liver complications. Previous studies have, however, been mainly from tertiary care centers, with risk for referral bias toward patients with worse outcomes. Furthermore, the impact of HDV viremia per se on liver-related outcomes is not really known outside the human immunodeficiency virus co-infection setting. We have therefore evaluated the long-term impact of HDV viremia on liver-related out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
113
2
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(136 citation statements)
references
References 33 publications
12
113
2
9
Order By: Relevance
“…124 The clinical features of CHD in immigrants have been studied in 2 large series, one of 1,112 immigrants in France, 125 and the other of 337 immigrants in Sweden. 126 In the French series the mean age of patients was 36.5 years; 77% had active HDV infection, based on increased aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels. Sub-Saharan patients were younger, more frequently overweight and less often abused alcohol; their geographic origin was reflected by the diversity of HDV genotypes, with the scarcely characterised HDV-5 accounting for 32.7%, HDV-7 for 5.3%, HDV-6 for 3.2% and HDV-8 for 2.7% of infections in these patients.…”
Section: Key Pointmentioning
confidence: 99%
“…124 The clinical features of CHD in immigrants have been studied in 2 large series, one of 1,112 immigrants in France, 125 and the other of 337 immigrants in Sweden. 126 In the French series the mean age of patients was 36.5 years; 77% had active HDV infection, based on increased aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels. Sub-Saharan patients were younger, more frequently overweight and less often abused alcohol; their geographic origin was reflected by the diversity of HDV genotypes, with the scarcely characterised HDV-5 accounting for 32.7%, HDV-7 for 5.3%, HDV-6 for 3.2% and HDV-8 for 2.7% of infections in these patients.…”
Section: Key Pointmentioning
confidence: 99%
“…Although a correlation between the levels of HDV replication and the risk of liver complications has been documented [ 20 , 40 ], there is limited information on the levels of HDV and HBV replication in patients with HDV-associated HCC. Even more limited are the data on the levels of HDV replication within the tumor and in the surrounding nontumorous tissue.…”
Section: Levels Of Hdv and Hbv Replication In Hcc-associated With Hdvmentioning
confidence: 99%
“…Approximately 5% of HBV carriers have been exposed to HDV, with a total of 15-20 million patients worldwide, although recent studies reported higher prevalence numbers [1][2][3]. HDV infection is associated with the most severe form of viral hepatitis with a twofold higher risk of developing cirrhosis, a threefold higher risk of developing hepatocellular carcinoma (HCC), and two fold increased mortality in comparison with HBV monoinfection [4][5][6]. Despite recent advances in the management of this condition, it still represents a significant medical burden [6][7][8].…”
Section: Introductionmentioning
confidence: 99%